2021
DOI: 10.2991/assehr.k.211223.214
|View full text |Cite
|
Sign up to set email alerts
|

Validity, Reliability, Intra-rater Instrument Parameter Teaching Factory and Learning Outcomes of Industrial Clothing

Abstract: The research aims to review the quality instrument of teaching factory parameters and learning outcomes instruments on fashion industry competence, especially internal consistency (Cronbach's alpha), reliability of retesting (Pearson correlation), and construct validity of existing parameters. Respondents were school principals and teachers involved in teaching factory management in a vocational high school for the Fashion Design skill program that taught factory learning, namely 30 people, while the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The item refinement was conducted on a five-point Likert scale before disseminating the questionnaire to the respondents [37]. Similarly, Cronbach's alpha was employed in previous studies for reliability assessment, which demonstrated  ISSN: 2252-8806 satisfactory overall internal consistency [39], [41], [42]. Nonetheless, focus group discussions were not performed in this study for the item generation.…”
Section: Discussionmentioning
confidence: 99%
“…The item refinement was conducted on a five-point Likert scale before disseminating the questionnaire to the respondents [37]. Similarly, Cronbach's alpha was employed in previous studies for reliability assessment, which demonstrated  ISSN: 2252-8806 satisfactory overall internal consistency [39], [41], [42]. Nonetheless, focus group discussions were not performed in this study for the item generation.…”
Section: Discussionmentioning
confidence: 99%
“…In a learning test, the score obtained is expected to be able to measure the actual ability (Budiastuti & Bandur, 2014). Measurement is the process of obtaining a score so that a person's measured ability truly describes the characteristics of that person (Suhartini et al, 2022). Test reliability is very important to determine the quality of the test.…”
Section: Reliability Testmentioning
confidence: 99%
“…It is crucial to ensure reliability and validity in surveys that utilize Likert-type scales before identifying the factor structure and beginning data analysis. In quantitative research, the Cronbach's alpha (Cα) value is widely used to evaluate reliability in social sciences [63][64][65][66]. The Cα value ranges from 0 to 1, and a value above 0.7 is considered sufficient for research purposes [67,68].…”
Section: Factor Structure and Data Analysismentioning
confidence: 99%